Some Notes on Procrastinate and Other Economy Matters - Nunes, Jairo (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
This paper argues that Chomsky's (1993) Procrastinate principle is not in consonance with the general guidelines of the Minimalist Program and proposes an alternative account of the preference for covert movement instead of overt movement and the preference for lexical insertion instead of movement. This proposal also accounts for the order of application of certain operations related to deletion of traces.